A review of organised crime in electronic finance. (16th April 2009) - Gottschalk, Petter; Dean, Geoff
Criminal Money Management (CMM) has received increased attention in recent years, as organised crime projects by criminal organisations apply transnational and global electronic finance to run their operations. The purpose of this article is to present the core topics relevant to our understanding of organised crime finances. This exploratory research includes topics such as hawala banking and hawala bankers transferring criminal proceeds, the enterprise paradigm of organised crime, the growth of criminal enterprises, a stage model for criminal organisations and the costs of crime for society. These topics are conceptually framed for the core issue of CMM in this article.